2007
DOI: 10.1002/pola.21947
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic simulation of single electron transfer–living radical polymerization of methyl acrylate at 25 °C

Abstract: A mechanistic comparison of the ATRP and SET‐LRP is presented. Subsequently, simulation of kinetic experiments demonstrated that, in the heterolytic outer‐sphere single‐electron transfer process responsible for the SET‐LRP, the activation of the initiator and of the propagating dormant species is faster than of the homolytic inner‐sphere electron‐transfer process responsible for ATRP. In addition, simulation experiments suggested that in both polymerizations the rate of deactivation is similar. In SET‐LRP, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
151
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(159 citation statements)
references
References 20 publications
8
151
0
Order By: Relevance
“…Although Percec and co-workers have demonstrated via kinetic simulations that in the heterolytic OSET process the activation of the initiator and of the propagating dormant species is faster than in an ISET process, 66 Zhong et al showed that the contribution of Cu(0) activation of alkyl halides to the overall polymerization is very small and thus it acts as a supplemental activator. Additional simulations based on experimentally measured rate coefficients showed that Cu(0) can also play the role of reducing agent as it is able to regenerate Cu I Br through comproportionation, and thus it was concluded that the SARA-ATRP mechanism can successfully describe these observations.…”
Section: Touching the Mechanistic Debatementioning
confidence: 98%
“…Although Percec and co-workers have demonstrated via kinetic simulations that in the heterolytic OSET process the activation of the initiator and of the propagating dormant species is faster than in an ISET process, 66 Zhong et al showed that the contribution of Cu(0) activation of alkyl halides to the overall polymerization is very small and thus it acts as a supplemental activator. Additional simulations based on experimentally measured rate coefficients showed that Cu(0) can also play the role of reducing agent as it is able to regenerate Cu I Br through comproportionation, and thus it was concluded that the SARA-ATRP mechanism can successfully describe these observations.…”
Section: Touching the Mechanistic Debatementioning
confidence: 98%
“…In this work, we describe the near-room temperature Cu(0)-mediated polymerization of MMA in toluene. As copper(I) complexes have previously been shown not to disproportionate in toluene, [26,27] we propose that this polymerization does not proceed by an OSET/instantaneous disproportionation mechanism. The mechanism of this particular system is under further investigation.…”
Section: Introductionmentioning
confidence: 95%
“…Under these conditions, and in agreement with the literature, >99% conversion in a few hours can be achieved with dispersities as low as 1.06 (Table 3, Entry 1, Figure S32). 35,62,63 However, having a universal set of conditions and reagents that would allow for the controlled polymerization of acrylates, methacrylates and styrene would be advantageous as it enables greater accessibility of polymeric materials by non-experts. As such, we were initially interested to explore whether IPA could afford the controlled polymerization of MA (maintaining EBiB and Me6Tren).…”
Section: The Synthesis Of Well Controlled Poly(acrylates) Under Univementioning
confidence: 99%